2013
DOI: 10.1093/nar/gks1477
|View full text |Cite
|
Sign up to set email alerts
|

Conformational rearrangements of RIG-I receptor on formation of a multiprotein:dsRNA assembly

Abstract: The retinoic acid inducible gene-I (RIG-I)-like family of receptors is positioned at the front line of our innate cellular defence system. RIG-I detects and binds to foreign duplex RNA in the cytoplasm of both immune and non-immune cells, and initiates the induction of type I interferons and pro-inflammatory cytokines. The mechanism of RIG-I activation by double-stranded RNA (dsRNA) involves a molecular rearrangement proposed to expose the N-terminal pair of caspase activation recruitment domains, enabling an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Based on multi-angle light scattering and sizeexclusion chromatography-coupled small-angle X-ray scattering of RIG-I/29mer dsRNA complexes, Beckham e al. suggested that binding of a first RIG-I molecule changes the RNA structure, thus constructively influencing the binding of a second RIG-I molecule (Beckham et al 2013).…”
Section: Triphosphate Independent Recognition Of Long Double Strandedmentioning
confidence: 99%
“…Based on multi-angle light scattering and sizeexclusion chromatography-coupled small-angle X-ray scattering of RIG-I/29mer dsRNA complexes, Beckham e al. suggested that binding of a first RIG-I molecule changes the RNA structure, thus constructively influencing the binding of a second RIG-I molecule (Beckham et al 2013).…”
Section: Triphosphate Independent Recognition Of Long Double Strandedmentioning
confidence: 99%
“…Multimerization of RIG-I on RNA has been observed using a variety of in vitro techniques [22][23][24]. However, the fact that several proteins can bind one RNA molecule does not mean that they are all functional, it does not mean that the proteins interact with each other and it does not imply that they bind cooperatively to RNA.…”
Section: Introductionmentioning
confidence: 99%
“…The production of almost all of the studied cytokines appears to be dependent on the concentration of Larifan used, with the efficacy of induction or suppression decreasing when higher concentrations are used. This “bell‐shaped” response type is well known in the context of dsRNA‐induced IFN production and can be explained by the activation mechanism that involves dimerization and multimerization with dsRNA molecules for most of the dsRNA detecting receptors . It is of interest that, among molecules suppressed by Larifan, there clearly appeared different concentration dependencies, with 200 µg/mL of Larifan being the most effective concentration for suppressing IL‐16 and 400 µg/mL for suppressing IP‐10 and SDF1‐a+b.…”
Section: Discussionmentioning
confidence: 96%